Cardiorespiratory fitness changes in patients receiving comprehensive outpatient cardiac rehabilitation in the UK: a multicentre study. Issue 11 (24th November 2012) - Sandercock, Gavin R H; Cardoso, Fernando; Almodhy, Meshal; Pepera, Garyfallia
Abstract : Background: Exercise training is a key component of cardiac rehabilitation but there is a discrepancy between the high volume of exercise prescribed in trials comprising the evidence base and the lower volume prescribed to UK patients. Objective: To quantify prescribed exercise volume and changes in cardiorespiratory fitness in UK cardiac rehabilitation patients. Methods: We accessed n=950 patients who completed cardiac rehabilitation at four UK centres and extracted clinical data and details of cardiorespiratory fitness testing pre- and post-rehabilitation. We calculated mean and effect size (d) for change in fitness at each centre and converted values to metabolic equivalent (METs). We calculated a fixed-effects estimate of change in fitness expressed as METs and d. Results: Patients completed 6 to 16 (median 8) supervised exercise sessions. Effect sizes for changes in fitness were d=0.34–0.99 in test-specific raw units and d=0.34–0.96 expressed as METs. The pooled fixed effect estimate for change in fitness was 0.52 METs (95% CI 0.51 to 0.53); or an effect size of d=0.59 (95% CI 0.58 to 0.60). Conclusion: Gains in fitness varied by centre and fitness assessment protocol but the overall increase in fitness (0.52 METs) was only a third the mean estimate reported in a recent systematic review (1.55 METs). The starkest difference in clinical practice in the UK centres we sampled and the trials which comprise the evidence-base for cardiac rehabilitation was the small volume of exercise completed by UK patients. The exercise training volume prescribed was also only a third that reported in most international studies. If representative of UK services, these low training volumes and small increases in cardiorespiratory fitness may partially explain the reported inefficacy of UK cardiac rehabilitation to reduce patient mortality and morbidity.